Prevalence and associated factors of musculoskeletal disorders among aquaculture workers in Vietnam: A cross-sectional study - Tran Thi Quynh, Chi; Nguyen Van, Tam; Nguyen Hoang Viet, Duc; Trieu Thi Thuy, Huong; Pham Van, Thuc (International Journal of Occupational Safety and Health, 2025)
Introduction: Aquaculture work is a physically demanding occupation with numerous risk factors for musculoskeletal disorders (MSDs), including exposure to cold water, heavy lifting, and repetitive tasks. This study aimed to determine the prevalence and associated factors of MSDs among aquaculture workers in Vietnam. Methods: A cross-sectional descriptive study was conducted involving 768 aquaculture workers aged 20 to 65 years. Participants were interviewed and clinically examined to assess their MSD status. The Nordic Musculoskeletal Questionnaire (NMQ) was utilized to assess symptoms of MSDs. Results: The prevalence of MSDs within the past seven days among aquaculture workers was found to be 61.5% (95% confidence interval [CI]: 58.1%–64.9%). The most commonly affected body regions were the lower back (43.6%), knee joints (35.2%), and wrists/hands (31.6%). Identified associated factors for MSDs included female gender (adjusted odds ratio [AOR] = 2.21, 95% CI: 1.64–2.97), work experience of 10 to 19 years (AOR = 1.43, 95% CI: 1.01–2.05) and over 20 years (AOR = 2.17, 95% CI: 1.45–3.19) compared to less than 10 years, being overweight or obese (AOR = 1.89, 95% CI: 1.26–2.79), working underwater (AOR = 3.01, 95% CI: 2.17–4.16), frequently lifting heavy loads (AOR = 2.92, 95% CI: 2.07–4.03), and regularly feeding seafood (AOR = 2.48, 95% CI: 1.83–3.33). Conclusion: MSDs are common health problems among aquaculture workers. To alleviate the burden of MSDs among aquaculture workers, its prevention should be integrated into occupational health policies, and evidence-based ergonomic interventions and improvements in working conditions must be implemented. Particular attention should be given to high-risk groups, including female workers, those with prolonged work hours, overweight individuals, and those performing physically demanding tasks.